Education and Empowerment - Rajashree S. Maranoor (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
Education is more than the simple transmission of knowledge; it is the cornerstone of personal growth, social transformation, and collective progress. Empowerment, on the other hand, is the process of enabling individuals or communities to gain control over their lives, make informed choices, and actively participate in society. The connection between education and empowerment is both direct and profound—education equips people with knowledge, skills, confidence, and critical thinking abilities that enable them to challenge inequalities and reshape their destinies. In modern societies, education has become not only a basic human right but also a crucial tool for empowerment across gender, caste, class, and regional divides. This article explores the multidimensional relationship between education and empowerment, analyzing its historical roots, contemporary importance, challenges, and transformative potential.